2014
DOI: 10.1364/ol.39.004899
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer holey plasmonic vortex lenses for the far field transmission of pure orbital angular momentum light states

Abstract: We report the design of a holey plasmonic vortex lens (PVL) structure able to couple circularly polarized impinging light to a plasmonic vortex in the form of the fundamental TM mode of a metal-insulator-metal plasmonic waveguide. The field transmitted through the hole milled at the center of the second metal layer of the structure is characterized by a well-defined spiral harmonic, entirely determined by the spin of impinging light and by the chirality of the PVL structure. Scattering finite elements simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…For the SPPs the grooves in the surface act as a source of SPPs and the vortex formation can be described by an interference pattern of waves running inside the spiral with the correct phase [2,3,5,7]. A similar equation for the vortex number has also been found [2,4,6,11,24,46]. In the SPP case the vortex manifests in the electric field perpendicular to the surface, while with our positive structure we obtain a vortex in the transverse components of the electric field.…”
Section: Mircometer-sized Spiralsupporting
confidence: 68%
See 1 more Smart Citation
“…For the SPPs the grooves in the surface act as a source of SPPs and the vortex formation can be described by an interference pattern of waves running inside the spiral with the correct phase [2,3,5,7]. A similar equation for the vortex number has also been found [2,4,6,11,24,46]. In the SPP case the vortex manifests in the electric field perpendicular to the surface, while with our positive structure we obtain a vortex in the transverse components of the electric field.…”
Section: Mircometer-sized Spiralsupporting
confidence: 68%
“…Recently it was shown that by grooving Archimedean spiral structures in a gold nano platelet, the surface plasmon polariton (SPP) field forms a vortex in the centre of the structure [1][2][3][4][5][6][7]. The femtosecond dynamics of the formation of the plasmonic vortex can be studied using time-resolved two-photon photoemission electron microscopy [8].…”
Section: Introductionmentioning
confidence: 99%
“…PVLs constitute a powerful tool to manipulate the topological charge of light, enabling to generate, modify and confine OAM 7 8 9 11 . In fact, PVLs not only transform the spin angular momentum (SAM) carried by an incident circularly polarized light beam into the OAM of the PV 17 18 19 20 , but can also impress in principle any amount of AM, depending of the chirality (namely, the number of spiral arms) of the PVL itself. Excited PVs propagating on the metal surface can then interact with nanostructures placed at the center of the PVL, exhibiting a number of interesting optical effects 7 8 9 10 11 .…”
mentioning
confidence: 99%
“…While from the perspective of functional nanostructures for generating OAM, it is evident that performance is imperfect, these measurements highlight that our powerful new measurement method allows for an unprecedented quantification. The performance of the nanostructures in terms of OAM mode purity can be further improved by optimizing the geometrical parameters of the spiral such as the aperture radius or by using metal–insulator–metal arrangements 45 , 46 . Our observation points out that the essential parameter to optimize is the tradeoff between overall transmission efficiency (requires large central aperture) and leakage into OAM = 0, ±2 (requires low direct transmission).…”
Section: Resultsmentioning
confidence: 99%